Seizure-Induced Hemoptysis in a Pediatric Patient - Ritika Nangia; Margaret Kahwaty; Ashutosh Sachdeva; Nidhi Kotwal (Case Reports in Pediatrics)
Hemoptysis can complicate seizures, albeit rarely. This unfamiliar presentation, reported infrequently in adults, can also affect children. This remains a rare clinical entity in pediatrics and we report one such case and its association with sterol carrier protein (SCP) gene mutation. We present a case of a 16-year-old male with recurrent episodes of hemoptysis following seizures. The diagnostic workup for etiology of the hemoptysis was unrevealing and he was ultimately treated for neurogenic pulmonary edema as a diagnosis of exclusion. He achieved complete resolution with supportive care and diuretics. Our case report describes the clinical and radiological presentation and overall management of post-ictal pulmonary hemorrhage and edema in a pediatric patient. In addition, it reports a new finding of possible association with sterol carrier protein (SCP2) carrier status. It also highlights a rare but potentially life-threatening consequence of inadequate seizure control in pediatric patients.